2021
DOI: 10.12688/wellcomeopenres.16259.4
|View full text |Cite
|
Sign up to set email alerts
|

A living mapping review for COVID-19 funded research projects: nine-month update

Abstract: Background: The coronavirus disease 2019 (COVID-19) has resulted in an unprecedented research response, demonstrating exceptional examples of rapid research and collaboration. There is however a need for greater coordination, with limited resources and the shifting global nature of the pandemic resulting in a proliferation of research projects underpowered and unable to achieve their aims. Methods: The UK Collaborative on Development Research (UKCDR) and Global Research Collaboration for Infectious Disease Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…When implemented at scale, these measures result in what is commonly known as a “lockdown”. While NPIs are evidenced to be effective at reducing COVID-19 transmission, mortality and healthcare demand ( Doung-Ngern et al , 2020 ; Ferguson et al , 2020 ; Flaxman et al , 2020 ; Koo et al , 2020 ), little social science research has been published on the psychosocial impact of lockdowns on the public ( Kittel et al , 2020 ; Norton et al , 2020a ), despite this being identified as a global priority research area ( Holmes et al , 2020 ; Norton et al , 2020b ; World Health Organization ).…”
Section: Introductionmentioning
confidence: 99%
“…When implemented at scale, these measures result in what is commonly known as a “lockdown”. While NPIs are evidenced to be effective at reducing COVID-19 transmission, mortality and healthcare demand ( Doung-Ngern et al , 2020 ; Ferguson et al , 2020 ; Flaxman et al , 2020 ; Koo et al , 2020 ), little social science research has been published on the psychosocial impact of lockdowns on the public ( Kittel et al , 2020 ; Norton et al , 2020a ), despite this being identified as a global priority research area ( Holmes et al , 2020 ; Norton et al , 2020b ; World Health Organization ).…”
Section: Introductionmentioning
confidence: 99%
“…One approach has been to focus on funders and attempt to identify the total number of research projects they funded and the amounts they allocated. In an inevitably challenging exercise, with Chinese data particularly difficult to secure, a UK and Canadian team created a global living mapping review of COVID-19 funded research projects [130]. Focusing on public and philanthropic funding, it found that the United States, the United Kingdom and Canada had the largest numbers of funded projects, with the same order for the amount of funding, except that in some editions Germany provided the third highest level.…”
Section: Lesson 4-evaluation: the Substantial And Immediate Benefits ...mentioning
confidence: 99%
“…The Global Coronavirus Innovation Map, Treatment and Vaccine Tracker, The COVID-19 Health Funding Tracker and many more. The large-scale application of various intervention measures was achieved by developing several digital IT applications and digital innovations with the aim of establishing a sustainable and effective method for reducing the risk of transmission and reaching optimal intervention and prevention strategies [22]. Furthermore, in the area of infection screening, artificial intelligence (AI), thermal cameras, and various smartphone applications were utilized in China, Taiwan, Singapore, and Iceland.…”
Section: Digital Industrial Sectormentioning
confidence: 99%